2017
DOI: 10.1364/oe.25.006936
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-supercontinuum source in the extreme ultraviolet using multiple frequency combs from high-harmonic generation

Abstract: A quasi-supercontinuum source in the extreme ultraviolet (XUV) is demonstrated using a table-top femtosecond laser and a tunable optical parametric amplifier (OPA) as a driver for high-harmonic generation (HHG). The harmonic radiation, which is usually a comb of odd multiples of the fundamental frequency, is generated by near-infrared (NIR) laser pulses from the OPA. A quasi-continuous XUV spectrum in the range of 30 to 100 eV is realized by averaging over multiple harmonic comb spectra with slightly different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…For the proof-of-concept study a SNSPD was illuminated with EUV radiation from an HHG source [40]. Figure 2a shows the experimental setup.…”
Section: Setupmentioning
confidence: 99%
“…For the proof-of-concept study a SNSPD was illuminated with EUV radiation from an HHG source [40]. Figure 2a shows the experimental setup.…”
Section: Setupmentioning
confidence: 99%
“…The XUV supercontinuum is generated by sweeping the driving OPA wavelength in the range of 1.22 − 1.32 m (in 10 nm steps). Such small variations of the wavelength are sufficient to shift the harmonic comb and fill the gaps in the HHG spectrum [19]. To filter out the XUV radiation from the remaining laser light, a 200 nm aluminum foil transmitting in the range of 33 − 72 eV has been used.…”
Section: Fig 1 (Left)mentioning
confidence: 99%
“…Although the applicability of synchrotron-based imaging methods is limited due to troublesome accessibility of the large-scale facilities, it has been shown that three-dimensional imaging of axial nanostructures is feasible [18]. However, in recent years, the rapid development of extremely broad bandwidth laser-driven XUV and SXR sources using the high-harmonic generation (HHG) [19] and laser-plasma sources (LPS) [20,21] has facilitated the realization of XCT at a laboratory scale [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Tunable HHG sources can increase the spectral coverage while maintaining a narrow linewidth and high flux, thus enabling to target specific resonances regardless of their spectral position. This holds immense potential for aforementioned spectroscopic techniques and has been employed for the generation of quasi-supercontinua [13]. Furthermore, tunable XUV sources are of great interest for lens-less XUV multispectral imaging.…”
mentioning
confidence: 99%
“…A large variety of spectrally tunable HHG sources have been demonstrated, often relying on manipulation of the driving laser field. Most intuitively, spectrally tunable infrared sources have been employed, either by high-order frequency mixing the weak but tunable output of OPG with a fixed-frequency high pulse energy laser inside the gas target [22,23], or by directly driving the HHG process with a tunable optical parametric amplifier (OPA) output [13,24,25]. Other approaches exploit the HHG spectrum's dependence on the driving laser intensity through blue-shifting [26], on the pulse chirp [27], or both [28].…”
mentioning
confidence: 99%